2000
DOI: 10.5565/publmat_44100_05
|View full text |Cite
|
Sign up to set email alerts
|

Maximal non-Jaffard subrings of a field

Abstract: A domain R is called a maximal non-Jaffard subring of a field L if R ⊂ L, R is not a Jaffard domain and each domain T such that R ⊂ T ⊆ L is Jaffard. We show that maximal non-Jaffard subrings R of a field L are the integrally closed pseudo-valuation domains satisfying dimv R = dim R + 1. Further characterizations are given. Maximal non-universally catenarian subrings of their quotient fields are also studied. It is proved that this class of domains coincides with the previous class when R is integrally closed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…In [3], the author and M. Ben Nasr considered maximal non-Jaffard subrings of a field L, that is, the domains R where R is a non Jaffard domain and each ring T , R ⊂ T ⊆ L is Jaffard. They characterized these domains in terms of pseudo-valuation domains.…”
Section: Throughout This Paper R → S Denotes An Extension Of Commutamentioning
confidence: 99%
“…In [3], the author and M. Ben Nasr considered maximal non-Jaffard subrings of a field L, that is, the domains R where R is a non Jaffard domain and each ring T , R ⊂ T ⊆ L is Jaffard. They characterized these domains in terms of pseudo-valuation domains.…”
Section: Throughout This Paper R → S Denotes An Extension Of Commutamentioning
confidence: 99%
“…Examples of such systems are the family of all S-overrings, that of all proper S-overrings, etc. (see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]). For a ring-theoretic property B and a ring extension R ⊂ S, let C denote the family of S-overrings T of R such that T does not satisfy B.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that if P is a ring-theoretic property and R ⊂ S are rings, then R is said to be maximal non-Psubring of S if R does not satisfy P, whereas T satisfies P for each ring T such that R ⊂ T ⊆ S, where the symbol "⊂" denotes proper inclusion. Recent studies of maximal non-P include (Ayache et al 2007; Ayache and Jarboui 2002;Ben Nasr and Jarboui 2000) in which the property P considered by the authors being ACCP, Noetherian or Jaffard, respectively. In Ayache and Jarboui (2002), the authors characterized maximal non-Noetherian subrings in several cases and they showed that if R is local and maximal non-Noetherian subring of S, then R is a pullback of the type R := (S, Q, D), where Q is a prime ideal of S but not necessarily a maximal ideal of S. Recall that a finite-dimensional integral domain R is said to be Jaffard if dim(R[X 1 , .…”
mentioning
confidence: 99%